HIGH FREQUENCY OF Ascaris lumbricoides IN PUBLIC PLAYGROUNDS IN CENTRAL BRAZIL - Fernandes Marinho, Renato; Cristina Evangelista Ferreira Sá, Lana; Castro, Nayara; Gurgel-Gonçalves, Rodrigo; Rodrigues Maldonade, Iriani; Rodrigues Machado, Eleuza (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Public playgrounds may be sources of parasite infections. This study analyzed the occurrence of intestinal parasites in playgrounds in the Federal District of Brazil (DF). Seventy sand samples were collected in 14 playgrounds distributed around the DF in 2015-2016 and were processed using the Willis and Hoffman methods. All playgrounds were contaminated with parasites. The parasites identified were Ascaris lumbricoides (33%), Strongyloides sp. (6%), Ancylostomidae (4%), Giardia sp. (4%), Trichuris sp. (3%) Toxocara sp. (3%) and Hymenolepis nana (1%). Results show the potential risk of transmission of parasitic diseases (mainly ascariasis) in playgrounds in central Brazil.